The Efficacy of Two Mycotoxin Detoxifications on Laying Performance, Antioxidant Capacity, and Liver Damage of Laying Hens Fed Diet Naturally Contaminated with Low-Level Mycotoxins - Huimin Ma; Wentao Cheng; Usman Nazir; Chengfei Wang; Haiming Yang; Xiaoli Wan (Veterinary Sciences, 2025)
This study was conducted to investigate the effects of two mycotoxin detoxifications on laying hens. A total of 360 70-week-old Hy-Line Brown laying hens were randomly divided into 1 of the 4 dietary treatment groups, with 6 replicates per group and 15 hens per replicate. The laying hens of the four treatments were fed with a basal diet (CON), a diet with naturally low-level mycotoxin contaminated corn (the levels of AFB1, ZEA, and DON in the corn of the CON group were 1.68 μg/kg, 42.75 μg/kg, and 585.40 μg/kg, respectively), replacing 73% of the corn in CON (MC), the MC diet with 1 g/kg modified silica-aluminate mycotoxin adsorbent (MA), and the MC diet with 1 g/kg mycotoxin degrading enzyme and bacteria complexes degradation agent (MD), respectively. Liver tissue and serum samples were extracted at the end of the trial to assess the antioxidant status and hepatic injury biomarkers. The experimental data were preliminarily interpreted in Excel and then analyzed by one-way ANOVA using SPSS, version 25 (SPSS Inc., Chicago, IL, USA). The results showed that compared to the CON, the MC group had decreased laying rate (p < 0.05), ferric reducing antioxidant potential in serum (p < 0.05), and reduced glutathione (GSH) content in the liver, and increased feed/egg ratio, serum alanine aminotransferase (ALT) activity, and malondialdehyde (MDA) content. Compared to the MC group, feed/egg ratio and serum ALT activity in the MA group and MD group decreased (p < 0.05), while serum GSH content and superoxide dismutase activity in the liver of the MA and MD groups increased. The liver glutathione peroxidase activity and the egg yolk percentage in the MA group decreased (p < 0.05) compared to the MC group. Histopathological alterations in liver tissues induced by mycotoxin included vacuolar degeneration, hepatocyte necrosis and disintegration, inflammatory cell infiltration, and enlarged hepatic sinuses. In short, both MA and MD were effective in mitigating the combined effects of low-level mycotoxins on laying hen performance, antioxidant capacity and liver damage.